Biodegradation of aflatoxin by peroxidase enzyme produced by local isolate of Pseudomonas sp. (International Journal of Scientific Research and Management (IJSRM), 2017)
Twenty isolates of bacterial isolates were screening for peroxidase activity. The isolate 13 was performance higher peroxidase activity among all isolates with activity (23 U/ml). The selected isolate was characterized and identified according to morphological and biochemical tests as Pseudomonas aeruginosa. The optimum pH for peroxidase activity was 6 with activity (42) U/ml. The result showed an increase in the activity at 40°C and peroxidase activity reached to (71) U/ml. The peroxidase from Pseudomonas sp able to degrade aflatoxin B1 after 24h and the maximum degradation (87%) was attained after 72 h at enzyme concentration 71 U/ml.